Análisis para la selección de sistemas de almacenamiento basados en baterías para microrredes eléctricas - Peña Suesca, Rafael Antonio; Santos León, Andrés Ignacio; Trujillo Rodríguez, César Leonardo (Ingeniería, 2020)
Context: In the implementation of a microgrid, the most expensive element is the energy storage system, which consists of batteries in most cases. Different authors, motivated to reduce the implementation costs that allow the widespread use of microgrids, have dedicated their efforts to develop techniques and topologies for microgrids, in order to optimize the energy storage system, seeking the compromise between useful life, maintenance, and initial investment. Context: In the implementation of a microgrid, the most expensive element is the energy storage system, which consists of batteries in most cases. Different authors, motivated to reduce the implementation costs that allow the widespread use of microgrids, have dedicated their efforts to develop techniques and topologies for microgrids, in order to optimize the energy storage system, seeking the compromise between useful life, maintenance, and initial investment. Method: The objective of this paper is to present the selection criteria used to select the type of battery in a microgrid, these being sufficient to ensure economic viability throughout the entire lifecycle of the system. To achieve this objective, papers indexed in journals of scientific and engineering content were consulted, classifying the criteria into two groups: technical criteria and technical-economic criteria. Results: It was established that the criteria ensure compliance with the technical characteristics required by the end-user of the micro-network, but they do not consider the operation of the storage system throughout its useful life. In contrast, the technical-economic criteria allow guaranteeing the operation of the microgrid storage system throughout the entire duration of the project. Conclusions: The classification of the criteria in this paper is a guide that allows motivating the progress of research to establish methodologies that guarantee viable implementation costs at the microgrid level, based on the technical-economic analysis of the storage system.